Peningkatan Literasi Bioinformatika bagi Siswa Sekolah Menengah melalui Pelatihan Implementasi Sains Data - Anuraga, Gangga; Fitriani, Fenny; Adawiyah, Rabiatul; Utami, Diva Aprilia Trisha; Faramaysty, Laura Sekar (Universitas Tribhuwana Tunggadewi Malang, 2025)
Bioinformatics is an interdisciplinary field that integrates biology, statistics, and computer science to analyze large-scale biological data. In the context of secondary education, students' understanding of this concept is still minimal. This study aims to evaluate the effectiveness of a training on the Implementation of Data Science in Bioinformatics, organized by the Statistics Study Program at Universitas PGRI Adi Buana Surabaya as part of a community service activity. The training methodology used a hybrid approach combining offline and online sessions. Twelfth-grade science students from five partner high schools participated. The training materials covered the basics of statistics, an introduction to bioinformatics, and biological data analysis case studies. The training showed increased participants' conceptual understanding and interest in data science. Furthermore, active interaction between students and speakers demonstrated the success of the participatory approach in learning activities. This activity also created collaborative relationships between partner universities and schools, extending the educational impact to secondary education environments. This training demonstrates the importance of integrating bioinformatics in secondary education to prepare young people to face the challenges of data-driven science.ABSTRAK Bioinformatika merupakan bidang interdisipliner yang mengintegrasikan biologi, statistika, dan ilmu komputer untuk menganalisis data biologis dalam skala besar. Dalam konteks pendidikan menengah, pemahaman siswa terhadap konsep ini masih sangat terbatas. Penelitian ini bertujuan untuk mengevaluasi efektivitas pelatihan bertema Implementasi Sains Data pada Bidang Bioinformatika yang diselenggarakan oleh Program Studi Statistika Universitas PGRI Adi Buana Surabaya sebagai bagian dari kegiatan pengabdian kepada masyarakat. Metodologi pelatihan menggunakan pendekatan hybrid yang menggabungkan sesi luring dan daring. Siswa kelas XII jurusan IPA dari lima SMA mitra dilibatkan sebagai peserta. Materi pelatihan mencakup dasar-dasar statistika, pengenalan bioinformatika, serta studi kasus analisis data biologis. Hasil pelatihan menunjukkan adanya peningkatan pemahaman konseptual dan minat peserta terhadap bidang sains data. Selain itu, terjadi interaksi aktif antara siswa dan narasumber yang mencerminkan keberhasilan pendekatan partisipatif dalam kegiatan pembelajaran. Kegiatan ini juga menciptakan hubungan kolaboratif antara universitas dan sekolah mitra, memperluas dampak edukatif ke lingkungan pendidikan menengah. Pelatihan ini membuktikan pentingnya integrasi bioinformatika dalam pendidikan menengah untuk mempersiapkan generasi muda menghadapi tantangan ilmu pengetahuan berbasis data.